Factors Influencing Financial Distress In Indonesian Healthcare and Energy Companies - Bella Dwimare Mamun; Ibeakamma Ugochinyere (Yayasan Az Zukhruf Cendikia, 2026)
Purpose – This study aims to examine and analyze the relationship between Total Asset Turnover, Audit Committee Characteristics, Working Capital Turnover, and Market Ratio and the financial distress condition of companies Design/methodology/approach – This study employs a quantitative approach using a sample of healthcare and energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Hypothesis testing is conducted using multiple regression analysis with the assistance of EViews 9 software. Findings – The results indicate that Total Asset Turnover has a positive but statistically insignificant effect on financial distress. Audit Committee Characteristics also show a positive but statistically insignificant effect on financial distress. In contrast, Working Capital Turnover has a negative and statistically significant effect on financial distress. Meanwhile, the Market Ratio has a negative but statistically insignificant effect on financial distress. Research limitations/implications – This research is limited to the observation period of 2022–2024, focusing on companies in the healthcare and energy sectors listed on the Indonesia Stock Exchange (IDX). This study examines total asset turnover, audit committee characteristics, working capital turnover, and market ratio as factors influencing corporate financial distress. The practical implication of this study is that the findings can serve as a reference for management and investors in assessing corporate financial performance and anticipating the risk of financial distress. JEL : G33, G30, M41